RETRACTED: Semiotic Analysis in Instagram Logo - Payuk, Eva Eriva Tandi; Zakrimal, Zakrimal (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in NOTION: Journal of Linguistics, Literature, and Culture to article entitled â€œSemiotics Analysis in Instagram Logoâ€ Vol 2, No 2, pp. 64-69, November 2020, DOI: https://doi.org/10.12928/notion.v2i2.2358.This paper has been found to be in violation of the NOTION Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Ideas: Journal on Language Teaching & Learning, Linguistics and Literature, Vol. 8, No. 1 (2020), DOI: 10.24256/ideas.v8i1.1383, entitled "Semiotics Analysis in Instagram Logo".The document and its content has been removed from NOTION, and reasonable effort should be made to remove all references to this article.